Determinants of Consumption Values and Their Impact on Green Purchase Intention through Green Trust: Case Study on the Purchase and Use of Xiaomi Electric Scooter Products in Jabodetabek - Deyna Dwitama Setiadi; Hari Muharam; Sufrin Hannan (Return : Study of Management, Economic and Bussines, 2024)
This study aims to analyze the determinants  of consumption value and  their impact  on green purchase intention through green trust in  a case study on the purchase and use of Xiaomi electric scooter products in Jabodetabek. This study used quantitative accidental sampling method by conducting survey techniques using questionnaire instruments. The questionnaire was distributed to 150 respondents in the Jabodetabek area and the classification of respondents were those who had known, had used, and had bought electric scooter products. The analysis techniques used are descriptive statistics and Structural Equation Modeling (SEM). The results of this study state that  consumption values  consisting of functional value, social value, and emotional value have a significant influence on green trust both individually  and  together, consumption values have a significant  influence on green purchase intention, green trust has a  significant influence on  Green Purchase Intention, as well as Consumption Values and  Green Trust together have a significant influence on Green Purchase Intention.